A STUDY ON THE PROTECTIVE EFFECT OF SILYBUM MARIANUM EXTRACT ON HEPATIC ISCHEMIA-REPERFUSION INJURY - Liu, Shaojun; Chen, Zhiheng; Cao, Dongbo; Liu, Fen; Wang, Xiaoyan; Zhao, Lian; Liu, Rui; Xiao, Zhiming (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of the study was to study the protective effect of Silybum marianum extract on hepatic ischemia-reperfusion injury. Rats were randomly divided into five groups; namely Silybum marianum extract high-, medium-, and low-dose protection groups, model group and control group. Hepatic ischemia-reperfusion injury model was prepared. Serum or plasma AST, ALT, MDA, TNF-α, IL-1β, IL-6 levels were measured. The results revealed that after liver injury, AST, ALT, MDA, TNF-α, IL-1β, and IL-6 levels significantly increased in succession, showing significant differences. We concluded that inflammatory cytokines participate in liver injury and that Silybum marianum extract can reduce the production of inflammatory cytokines, and thus can have a protective effect on hepatic ischemia and reperfusion.